Cyberbullying, conflict management or just messing? Teenage girls' understandings and experiences of gender, friendship, and conflict on Facebook in an Irish second-level school. Issue 5 (2nd September 2016) - Ging, Debbie; O'Higgins Norman, James
Abstract: In recent years, there have been growing concerns worldwide about young people's safety online, much of which focuses on social media sites such as Facebook and Instagram. Moral panics about sexting and cyberbullying have constructed public discourses about social media as dangerous to adolescents' safety and relationships. In the academic literature, there are conflicting perspectives on the nature of online relationships, behaviour, and risks, and on the causes and nature of cyberbullying. Less attention is paid—in both public and academic debates—to the role played by gender in online aggression, in spite of the fact that existing scholarship demonstrates that it is an important factor in the dynamics of young people's online friendships and conflicts. This article presents the findings of an empirical, qualitative and quantitative study of teenage girls' experiences and understandings of online friendship, conflict, and bullying in an Irish, single-sex secondary school. Questionnaires ( n =116), individual in-depth interviews with students ( n =26), and a focus group with teachers were used. Our study indicates that significant communicative phenomena within girls' everyday lives remain unreported and frequently misunderstood.